Accommodating standardized patient exams: The OSCEs. Issue 4 (November 2016) - Meeks, Lisa M.; Jain, Neera R.
Abstract : We are often asked whether students should receive accommodations on standardized patient or "practical" exams, sometimes referred to as OSCEs, or Objective Structured Clinical Examinations. Programs are often concerned about the reasonable nature of these requests and transferability of accommodations in the clinical setting. However, it is important to engage in the interactive process for all disability requests — including those with a clinical component.